Synthesis of New 3-[(Alkylthio)methyl]-1-hydroxy-2-phenylindoles - Lee, Sang Hyup; Kim, Hyejin; Park, Yeon Kyeong; Cho, Hyunsung (Synlett, 2015)
The syntheses of new 3-[(alkylthio)methyl]-1-hydroxy-2-phenylindoles are presented. The substrates, obtained by efficient three-step synthesis, were treated with various thiol nucleophiles in the presence of SnCl2·2H2O to provide target compounds, through the consecutive processes of reduction, condensation, and addition in one pot. The mechanistic studies on reaction pathways and the involved intermediates are described.
Keywords: indoles; heterocycles; nucleophilic addition; tin; reduction